2021
DOI: 10.3390/ijerph18179210
|View full text |Cite
|
Sign up to set email alerts
|

To Vaccinate or Not to Vaccinate—This Is the Question among Swiss University Students

Abstract: The speed and innovation of the COVID-19 vaccine development has been accompanied by insecurity and skepticism. Young adults’ attitude to vaccination remains under investigation, although herd immunity cannot be reached without them. The HEalth in Students during the Corona pandemic study (HES-C) provided the opportunity to investigate vaccination intention in 1478 students in the sixth survey wave (January 2021), including vaccination intention, psychological antecedents of vaccine hesitancy, trust in governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
3
25
2
Order By: Relevance
“…38 Participants who had a history of vaccination reluctancy for their children were considerably less likely to take the COVID-19 vaccine. This finding revealed that respondents with a previous history of vaccine uptake were two times more likely to accept COVID-19 vaccine (AOR: 2.534, 95% CI: 1.412, 4.549) than their corresponding groups which was in line with the study conducted in Uganda, 53 Switzerland, 54 New Jersey, 33 and Jordan. 55 The vaccine hesitancy affects both the person who refuses to take the vaccine and the entire population, posing a significant challenge to reaching the threshold for conferring COVID-19 herd immunity.…”
supporting
confidence: 86%
“…38 Participants who had a history of vaccination reluctancy for their children were considerably less likely to take the COVID-19 vaccine. This finding revealed that respondents with a previous history of vaccine uptake were two times more likely to accept COVID-19 vaccine (AOR: 2.534, 95% CI: 1.412, 4.549) than their corresponding groups which was in line with the study conducted in Uganda, 53 Switzerland, 54 New Jersey, 33 and Jordan. 55 The vaccine hesitancy affects both the person who refuses to take the vaccine and the entire population, posing a significant challenge to reaching the threshold for conferring COVID-19 herd immunity.…”
supporting
confidence: 86%
“…Lack of trust in authorities and pharmaceutical companies has also been reported in other studies [ 41 , 51 , 52 ]. Strengthening trust, however, is crucial [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 5C model has subsequently become an important tool for measuring the determinants of vaccine hesitancy, and has been used for this purpose on various populations in different countries, including Hong Kong nurses ( 11 ); USA patients ( 12 ); German physicians ( 13 , 14 ); Bangladeshi adults ( 15 ); Swiss university students ( 16 ); and adults in Egypt, United Arab Emirates and Jordan ( 17 ). Although South Africa is yet to validate a tool for measuring the extent and determinants of vaccine hesitancy, there is evidence from South Africa that the 5C tool may be appropriate for investigating HPV vaccine hesitancy in this setting ( 8 ).…”
Section: Methodsmentioning
confidence: 99%